Data to the paper "Effect of targeted acetylation on wood-water interactions at high moisture states" - Fredriksson, Maria; Digaitis, Ramunas; Engqvist, Jonas; Thybring, Emil (Lund University, 2023)
The data set include data from Low Field Nuclear Magnestic Resonance (LFNMR) measurements and Differential Scanning Calorimetry (DSC) measurements for different types of acetylated wood (Norway spruce) conditioned at several moisture levels in the over-hygroscopic moisture range. Cell wall moisture contents and capillary water moisture contents were evaluated from the data. The data set and the content of the different files are further described in the document "readme.txt".

Inkluderar data från lågfälts-NMR mätningar och mätningar med "Differential Scanning Calorimetry" (DSC) för olika typer av acetylerat trä (gran) som konditionerats till olika fukttillstånd i det över-hygroskopiska fuktområdet. Från denna data har cellväggskvot och kapillär fuktkvot utvärderats. Datan samt innehållet i de olika filerna beskrivs vidare i dokumentet "readme.txt".
Data till artikeln "Effect of targeted acetylation on wood-water interactions at high moisture states"
Keywords: wood; trä; materials science; materialvetenskap; sorption; sorption; wood technology; träteknologi; wood chemistry; träkemi; wood modification; trämodifiering; pressure plate; pressure plate; Other Civil Engineering; Annan samhällsbyggnadsteknik; Paper, Pulp and Fiber Technology; Pappers-, massa- och fiberteknik; Other Materials Engineering; Annan materialteknik